New high-gain continuous controller scheme for a class of uncertain nonlinear systems - Kuvulmaz, Janset; Zergeroğlu, Erkan (IEEE, 2007)
In this study, we present a new continuous controller mechanism for the tracking problem of uncertain non-linear systems. The proposed strategy is based on a Lyapunov-based stability argument and only requires the uncertainties of the dynamical system to be first order differentiable to achieve asymptotic tracking. For the ease of presentation the controller formulation is presented on a general, second order single-input single-output dynamical system, however extension to multi-input multi-output and higher order versions are also possible with a considerably small effort Simulation studies on a two link planar robot system are presented to illustrate the feasibility of the proposed strategy.
46th IEEE Conference on Decision and Control -- DEC 12-14, 2007 -- New Orleans, LA